2015
DOI: 10.1111/jomf.12249
|View full text |Cite
|
Sign up to set email alerts
|

Family Flexibility in Response to Economic Conditions: Fathers' Involvement in Child‐Care Tasks

Abstract: TasksRecession-related increases in men's child care are well documented, but supporting evidence describes the last several decades of the 20th century. Changes in family life and in the association between families' economic conditions and the macro economy provide reason to question the continued existence of a "recession effect." This article evaluates the frequency of married and cohabiting fathers' engagement in the day-to-day tasks of child care during the so-called Great Recession, using data from male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 12 publications
1
10
0
1
Order By: Relevance
“…Results from the content analysis of study findings revealed that approximately 32% of studies examined fathers' involvement in some element of food work (eg, shopping, cooking, feeding the child), 62% examined the specific food parenting practices fathers adopted and 5% of studies examined both. Overall, studies examining fathers' involvement in food work show that, although fathers are involved 35‐38 and their involvement has increased over time, 39 their involvement is lower than mothers 40‐49 . In addition, while fathers see their role in household food work as important, 38,50,51 full‐time employment and work pressures are common barriers to their participation 52,53 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from the content analysis of study findings revealed that approximately 32% of studies examined fathers' involvement in some element of food work (eg, shopping, cooking, feeding the child), 62% examined the specific food parenting practices fathers adopted and 5% of studies examined both. Overall, studies examining fathers' involvement in food work show that, although fathers are involved 35‐38 and their involvement has increased over time, 39 their involvement is lower than mothers 40‐49 . In addition, while fathers see their role in household food work as important, 38,50,51 full‐time employment and work pressures are common barriers to their participation 52,53 .…”
Section: Resultsmentioning
confidence: 99%
“…Previously, it was noted that most studies examining fathers' food parenting included less than 100 fathers 91 . This difference may be explained by several recent studies that included large (>1500) samples of fathers 35,39 . In addition, there is some suggestion that there is greater diversity in study samples.…”
Section: Discussionmentioning
confidence: 99%
“…Concern about these data gaps and broad interest in father involvement motivated newer surveys of men that include both measures of men's pregnancy intentions and fathering behaviors, such as the NSFG and the Early Childhood Longitudinal Survey–Birth Cohort (ECLS‐B; Cabrera et al, ). Although the inclusion of men in the NSFG has facilitated separate inquiry into both men's childbearing intentions (Lindberg & Kost, 2013) and their fathering behaviors (Jones & Mosher, ; Knop & Brewster, ; Yoshida, ), no studies to date have examined the intersection of these two areas using these nationally representative data.…”
Section: Introductionmentioning
confidence: 99%
“…Экономические условия рассматриваются исследователями в качестве факторов формирования отцовского поведения: низкий уровень доходов, как правило, коррелирует с низкой вовлеченностью отцов в заботу о детях. Б. Кноп и К. Брюстер, используя данные мужчин-респондентов из национального обследования развития семьи 2012-2015 гг., показали, что в период экономической рецессии доля вовлеченных в уход отцов резко упала, но стала восстанавливаться в последующие годы [Knop, Brewster, 2016].…”
Section: теоретические основания исследованийunclassified